1984
DOI: 10.1093/carcin/5.12.1565
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid: a potent naturally occurring inhibitor of benzo[a]pyrene metabolism and its subsequent glucuronidation, sulfation and covalent binding to DNA in cultured BALB/C mouse keratinocytes

Abstract: The metabolism of [3H]benzo[a]pyrene (BP) by cultured primary keratinocytes prepared from BALB/C mouse epidermis was found to be largely inhibited by the dietary plant phenol, ellagic acid. Varying concentrations of ellagic acid added to the keratinocyte cultures resulted in a dose-dependent inhibition of the cytochrome P-450-dependent monooxygenases aryl hydrocarbon hydroxylase (AHH) and 7-ethoxycoumarin-O-deethylase (ECD). The major organic solvent-extractable metabolites found intracellularly in the culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In fact, Dixit and Gold [ 19861 and Barch and Fox [ 19881 showed that ellagic acid protects the 0 6 position of DNA guanine against the methylation capacity of MeNU and MBN; Lord et al [1989] showed no inhibitory effect of DMN mutagenicity. Furthermore, studies support the ability of ellagic acid to reduce the metabolism of some polycyclic aromatic hydrocarbons [Mukhtar et al, 1984;Das et al, 1985;Tee1 et al, 19851, but not of nitropyrene [Kuo et al, 19921, and to counteract their diol epoxide metabolites [Wood et al, 1982;Dixit et al, 1985;Josephy et al, 19901, inhibiting their binding to DNA.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Dixit and Gold [ 19861 and Barch and Fox [ 19881 showed that ellagic acid protects the 0 6 position of DNA guanine against the methylation capacity of MeNU and MBN; Lord et al [1989] showed no inhibitory effect of DMN mutagenicity. Furthermore, studies support the ability of ellagic acid to reduce the metabolism of some polycyclic aromatic hydrocarbons [Mukhtar et al, 1984;Das et al, 1985;Tee1 et al, 19851, but not of nitropyrene [Kuo et al, 19921, and to counteract their diol epoxide metabolites [Wood et al, 1982;Dixit et al, 1985;Josephy et al, 19901, inhibiting their binding to DNA.…”
Section: Discussionmentioning
confidence: 97%
“…Ellagic acid has been shown to lower total P450 content of rat hepatic (16), lung (16) and esophageal microsomes (17). It has also been shown to inhibit the bioactivation of procarcinogens which are metabolized by the P4501A family, including BaP, 3-methylcholathrene (3-MC), and the food mutagen 2-amino-3-methylimidazole [4,5-t] quinoline (IQ) (18)(19)(20). Furthermore, it has been reported that dietary ellagic acid significantly reduces total esophageal and hepatic P450 levels and the esophageal microsomal metabolism of NMBA (17).…”
Section: Ellagic Acidmentioning
confidence: 99%
“…Geraniin (1), upon hydrolysis in boiling water, gives corilagin (2), ellagic (3), gallic (4) and brevifolincarboxylic (5) acids in addition to glucose, while upon acid hydrolysis it provides 3 and 4 [8] (Figure 1). Compounds 1-5 have strong antioxidant activities [2][3][4][5], ellagic acid (3) is a potent inhibitor of benzo[a]pyrene metabolism [9], has activity against SUDHL1 and FEPD tumor cells, and is a casein kinase 2 inhibitor [10], and methyl gallate (6) inhibits the growth of B16 melanoma, L1210 and P388 tumor cells [11].…”
mentioning
confidence: 99%